Perancangan Jaringan Lte-Advanced Menggunakan Metode Carrier Aggregation Inter band Non-Contiguous - Gemilang, Hafiz Pradana; Oktavianasari, Linna (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Long Term Evolution Advanced (LTE-A) is a technology based on designed IP as a fast communications service solution. LTE frequency allocation in Indonesia is very limited, so it required reusing or combining options of frequencies will be used. Purpose of this research is to know the comparison of network quality between Carrier Aggregation (CA) and non-Carrier Aggregation (Non-CA). CA is a feature can combine two or more carrier components with a maximum bandwidth 20 MHz. In this research, LTE-A network designed compare performance of frequency by using interband-non-contiguous CA technique and without CA. Frequency bands used are 900 MHz and 1800 MHz. The results of simulation show that CA Technique provide a throughput of 201,925 Mbps compare to 161,382 Mbps for non-CA at 900 MHz and 1800 MHz. The CA also provide the 100% of user connected. Coverage by signal level on CA Method is superior to 98.47% with signal value â‰¥- 80 dBm, whereas in non-CA technique, it has diverse result because using different propagation model produces different cell radius value. Some above parameters show that design result with CA technique is superior to Non-CA. So based on these parameters can be concluded that CA is suitable to be applied in Indonesia.Keywords: LTE, LTE-A, Carrier Aggregation, Signal Level, Interband Non-Contiguous, Bandwidth.